AN ANALYSIS OF HUMAN RESOURCE INFORMATION SYSTEM MANAGEMENT ON COMPANY PERFORMANCE - Bayu Rama Laksono; Sofie Yunida Putri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This investigation plans to decide the administration of HR data frameworks at CV. Samaco, which is occupied with development administrations, is to discover how much impact HR data frameworks have on organization execution. The exploration method was to convey surveys to representatives with a populace of 60 workers, but since specialists zeroed in on research on development representatives, the examples taken were 30 representatives. The consequences of this examination demonstrate that HR data framework administration affects organization execution. In this structure, the ends that can be acknowledged from this examination are that the speculation can be acknowledged and its legitimacy is demonstrated. This demonstrates that the better the execution of human asset data framework administration, the better the organization execution CV. Samaco